My Life in Focus : A Photographer's Journey with Elizabeth Taylor and the Hollywood Jet Set - Bozzacchi, Gianni; Tayler, Joey (Screen classics (Lexington, Ky.), 2016)
When Gianni Bozzacchi accepted an assignment as a photographer on the set of The Comedians (1967), he didn't know that his life was about to change forever. His ability to capture the beauty of candid moments drew the attention of the film's star, Elizabeth Taylor, and prompted her to hire him as her personal photographer. Not only did he go on to enjoy a jet-set life as her friend and confidant preserving unguarded moments between the violet-eyed beauty and Richard Burton as they traveled the world but Bozzacchi also became an internationally renowned photographer and shot some of the biggest celebrities of the 1960s and 1970s. In My Life in Focus, Bozzacchi traces his journey from humble beginnings to the sphere of the rich and famous. As a child, he cultivated his skills by working with his father a photographer for the Italian government. Following in his parent's footsteps was not something Bozzacchi had foreseen for his future; but his passion for taking pictures and his ability to put his subjects at ease enabled him to capture stunning images of some of the greatest stars of the twentieth century, including Audrey Hepburn, Steve McQueen, Raquel Welch, Mia Farrow, Clint Eastwood, and the royal family of Monaco. Beautifully illustrated with many of the photographer's most iconic images, this lively memoir reveals private moments in the Taylor-Burton love story and provides an invaluable behind-the-scenes look at the business of filmmaking and the perils of celebrity.